1997
DOI: 10.1164/ajrccm.156.1.9608084
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Platelet-activating Factor Acetylhydrolase in Human Bronchoalveolar Lavage

Abstract: Platelet-activating factor (PAF) is a mediator produced in human airways during acute and chronic inflammatory lung diseases. The levels of PAF are regulated by acetylhydrolase (AH), the enzyme that converts PAF to lyso-PAF. To determine whether AH was present in human bronchoalveolar lavage (BAL) fluid, BAL was obtained from normal donors (n = 18) and from adult patients with mild bronchial asthma (n = 15) or with lung fibrosis (n = 15). AH activity was consistently found in the cell-free BAL fluid. BAL-AH is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Plasma PAF-AH is produced by cells of hematopoetic origin, predominantly macrophages, and its expression can be downregulated by LPS and certain cytokines (3,118). A deficiency of PAF-AH in the BALF of asthmatic patients compared to the level in healthy patients may prolong PAF activity and represent an underlying mechanism contributing to the asthmatic pathology (120). A point mutation in the plasma PAF-AH gene (V279F) results in an inactive enzyme and has been identified in patients from Japan.…”
Section: Paf-ahsmentioning
confidence: 99%
“…Plasma PAF-AH is produced by cells of hematopoetic origin, predominantly macrophages, and its expression can be downregulated by LPS and certain cytokines (3,118). A deficiency of PAF-AH in the BALF of asthmatic patients compared to the level in healthy patients may prolong PAF activity and represent an underlying mechanism contributing to the asthmatic pathology (120). A point mutation in the plasma PAF-AH gene (V279F) results in an inactive enzyme and has been identified in patients from Japan.…”
Section: Paf-ahsmentioning
confidence: 99%
“…In selected experiments we used macrophages isolated from the bronchoalveolar lavage of patients undergoing diagnostic bronchoscopy for lung carcinoma. The bronchoalveolar lavage procedure and the isolation of macrophages were previously described (29). The cells were then incubated in 24-well plates (Falcon, Becton Dickinson, Franklin Lakes, NJ) at 37°C in a humidified atmosphere of 5% CO 2 and 95% air.…”
Section: Isolation and Purification Of Human Lung Macrophagesmentioning
confidence: 99%
“…5 Plasma PAF-AH (pPAF-AH) has a relatively broad substrate specificity for phospholipids, and can catalyze and inactivate not only PAF but also PAF-like oxidized lipids. 6 This enzyme activity has been reported to correlate with several inflammatory diseases such as asthma, 7,8 systemic lupus erythematosus 9 and juvenile rheumatoid arthritis. 10 Furthermore, previous reports have revealed that the polymorphism of pPAF-AH gene (PLA2G7) influences its activity.…”
Section: Introductionmentioning
confidence: 99%